Developing Salinity-Tolerant Hybrid Rice Parental Lines through Integrative Breeding and Molecular Approaches - Quddus, M R; Rahman, M A; Hasan, M; Rasul, M G; Mannan, M A; Hasan, M J (Bangladesh Rice Journal, 2026)
Salinity stress is a major abiotic constraint limiting rice production in coastal and irrigated ecosystems, affecting approximately 20% of global agricultural land. Developing salinity-tolerant hybrid rice parental lines is critical for sustaining productivity in salt-affected areas, yet systematic efforts integrating tolerance traits with fertility restoration or maintenance ability remain limited. This study reports the development of 49 new salinity-tolerant hybrid rice parental lines through strategic crossing, Best Linear Unbiased Prediction (BLUP)-based selection, and integrated molecular–phenotypic validation. A total of 286 genetically fixed entries derived from 22 crosses among the parental lines (14 maintainer × maintainer and 8 restorer × restorer), along with 19 elite lines, were evaluated under salinity stress environment. Parental lines with Standard Evaluation Score (SES) values of 3–5 were strategically crossed and advanced through field rapid generation advance (FRGA). BLUP-based selection identified 54 superior genotypes exceeding the population mean plus one standard deviation for yield. Salinity tolerance was further confirmed through screening under 12 dS/m stress at the seedling stage, which identified 10 highly tolerant parental lines (SES 3) and 19 moderately tolerant parental lines (SES 5). Molecular marker analysis using DRRM-Rf3-5 and DRCG-RF4-14 markers, coupled with test cross pollen fertility testing, successfully validated 25 maintainer lines and 24 restorer lines. Ward's D2 hierarchical clustering classified the selected lines into three distinct clusters representing late-maturing high-yielding, medium-duration tall, and early-maturing high-tillering ideotypes. These newly developed parental lines provide valuable genetic resources for breeding high-yielding, salinity-tolerant hybrid rice varieties suited to salt-affected ecosystems, thereby contributing to sustainable rice production and enhanced food security. Bangladesh Rice J.28(1): 17-39